Answer :

First solving (x – 3)(x + 3)

Using the identity (a +b) (a–b) = a2 – b2


Here a = x and b = 3


= x2 –32


= x2 – 9


Now (x2 – 9) (x2 + 9)


Again, using the identity (a +b) (a–b) = a2 – b2


Here a = x2 and b = 9


= (x2)2 – 92


= x4 –81 ( (ax)m = axm)


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Find the product:Karnataka Board - Mathematics Part I

If a, b are ratioKarnataka Board - Mathematics Part I

Use the identity Karnataka Board - Mathematics Part I

Express the folloKarnataka Board - Mathematics Part I

Find the product:Karnataka Board - Mathematics Part I

Simplify:

Karnataka Board - Mathematics Part I

Find the product:Karnataka Board - Mathematics Part I

Find the product:Karnataka Board - Mathematics Part I

Evaluate these usKarnataka Board - Mathematics Part I

Find the product:Karnataka Board - Mathematics Part I